2015
DOI: 10.1111/acer.12859
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Chronic Ethanol Consumption and Thiamine Deficiency on Neural Plasticity, Spatial Memory, and Cognitive Flexibility

Abstract: Background Many alcoholics display moderate to severe cognitive dysfunction accompanied by brain pathology. A factor confounded with prolonged heavy alcohol consumption is poor nutrition and many alcoholics are thiamine deficient. Thus, thiamine deficiency (TD) has emerged as a key factor underlying alcohol–related brain damage (ARBD). TD in humans can lead to Wernicke Encephalitis that can progress into Wernicke–Korsakoff Syndrome and these disorders have a high prevalence among alcoholics. Animal models are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…Hippocampal tissue was diluted at a ratio of 1:4, while frontocortical was diluted at a ratio of 1:5 for appropriate detection within a standard curve. Protocol details can be found in Vedder et al, 2015. Homogenate samples (198) were run in duplicate across multiple days, therefore water i.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal tissue was diluted at a ratio of 1:4, while frontocortical was diluted at a ratio of 1:5 for appropriate detection within a standard curve. Protocol details can be found in Vedder et al, 2015. Homogenate samples (198) were run in duplicate across multiple days, therefore water i.g.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that prenatal and adult chronic EtOH exposure alters levels of neurotrophin, such as brain derived neurotrophic factor (BDNF), in the frontal cortex and hippocampus (Miller et al, 2002; Davis, 2008; Nixon and McClain, 2010; Mooney and Miller, 2011; Vedder et al, 2015). However, few studies have assessed neurotrophin expression after adolescent CIE and the results are variable (Briones and Woods, 2013; McClain et al, 2014; Sakharkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, thiamine deficiency resulting from chronic alcohol is also associated with general alcohol neurotoxicity and cerebellar degeneration without WKS (Martin et al, 1994). In addition, a subclinical thiamine deficiency during chronic heavy alcohol consumption can lead to significant cognitive impairments and reduced neuroplasticity (Vedder et al, 2015). The moderate association between a TPK1 SNP and alcohol dependence (Bierut et al, 2010), is supported by previous work showing a link between thiamine deficiency, neuropathology and associated cognitive impairments in cases of chronic alcohol consumption.…”
Section: Genome-wide Association Studies Of Alcohol Dependencementioning
confidence: 99%
“…A rodent model of WKS, pyrithiamine-induced thiamine deficiency (PTD), recapitulates the diencephalic pathology observed in WKS patients, including damage to the mammillary bodies, anterior thalamic nuclei, and midline thalamic nuclei (Mair 1994;Langlais et al 1996). The PTD model also exhibits deficits in spatial working memory that persists for months after recovery from TD (Pitkin and Savage 2004;Vedder et al 2015).…”
mentioning
confidence: 95%
“…There is a long-term decrease in hippocampal BDNF levels in the TD model (Vedder et al 2015;Hall and Savage 2016). Methods such as exercise and environmental enrichment that increase hippocampal BDNF levels have been demonstrated to improve hippocampal neural plasticity as well as learning and memory performance (Bekinschtein et al 2011;Chourbaji et al 2011).…”
mentioning
confidence: 99%